Strategi Pemasaran Bekatul Beras Merah Instan di CV. Pantiboga Natural Food Specialist, Kecamatan Matesih, Kabupaten Karanganyar - Widya Ayu Pradani; Mohamad Harisudin; Isti Khomah (Agriecobis : Journal of Agricultural Socioeconomics and Business, 2021)
CV. Pantiboga Natural Food Specialist is a producer of processed products made from brown rice bran and spices, named “Red Bran” instant red rice bran. During running the business, CV. Pantiboga Natural Food Specialist ihas several problems related to product marketing. This study aims to identify strengths, weakness, opportunities, and threats, formulate alternative marketing strategies, and determining priority strategies that can be applied in the marketing of instant brown rice bran. The basic method used is descriptive analysis. The types of data used are primary and secondary data. Methods of data analysis using matrix analysis of IFE, EFE, Grand Strategy, SWOT, and QSPM. The results of this research show the IFE matrix analysis at CV. Pantiboga Natural Food Specialist is strong in utilizing strengths and overcoming weakness. The EFE matrix also shows that CV. Pantiboga Natural Food Specialist is strong in taking advantage of opportunities and avoiding threats. The SWOT position is in quadrant 1 which supports the company in pursuing an aggressive strategy. The SWOT matrix results obtained four alternative strategies which were then assessef for their attractiveness in the QSPM matrix. The value of attractiveness (TAS) shows the strategic priority by improving product quality in order to maintain customer loyalty and acquire new customers